(untitled) (Revista Educação, Artes e Inclusão, 2025)
Culture and sustainability are fundamental dimensions of the contemporary societies’ development.Sociocultural processes are fundamental in the creation of sustainable actions, as they contributeto the development of inclusive societies and promote supportive relationships between groups ofdifferent identity origins. Our objective in this article is to discuss the conceptual and practicalrelationships between culture and sustainability from a perspective that includes culturemanagement, actions and voices of creators and makers of culture in the Brazilian Amazon regionwith sustained development. As a methodological procedure, we used scientometric indicators ofproductions by researchers and scholars who focused their investigations and publications on thetheme of the Brazilian Amazon. The themes investigated in the collection of information refer tosustainability, sustainable development, and culture. The data allowed us to analyze sustainabledevelopment practices. However, when we relate the topic to culture, the data highlighted thescarcity of discussion on the subject, especially in the Amazon region. Yet, the results allow us toconsider that cultural practices, nature conservation and sustained development in the BrazilianAmazon region are pillars that guarantee a healthy relationship between nature and the profusedevelopment of local communities.